Residential Care in Italy: Critical Issues and Future Perspectives. Issue 1 (2nd January 2016) - Ghio, Lucio; Favaretto, Gerardo; Rocca, Gabriele; Calcagno, Pietro; Pacella, Sara; Ferrannini, Luigi
Abstract: As a result of law 180/78, a community-based model of mental health care was developed and the first nonhospital residential facilities were implemented, following specific principles that had been formulated for therapeutic communities in Italy. Taking into account the new national guidelines in this field, the purpose of this article is to describe the development over the years of residential facility care in Italy, to address the critical issues that have emerged, and to outline the future developments. The main critical issues that have emerged are: the gradually increasing of the number of facilities from 2000 to present, the low rate of discharge with the consequent risk of institutionalisation, the high variability of resources and interventions provided by facilities, the low adherence to national guidelines, and the poor differentiation of levels of intensity of care offered. In relation to this critical data, a national plan of recommendations was set up by the Ministry of Health in 2013. The aim was to promote a move from the logic of long-term stays to that of individualized and project-based care pathways and to distinguish residential facilities based on the level of rehabilitation intervention and intensity of assistance offered. The new plan should promote an improvement of the quality of care of residential facilities; however, more efforts should be addressed to the understanding of what are the factors related to a successful conclusion of residential treatments.